Resources for Psychological Safety of Students in an Unstable Sociocultural Environment: a Review of Theoretical and Empirical Research - I.A. Baeva; E.B. Laktionova; I.V. Kondakova; J.S. Pezhemskaya; M.-; Yu.S. Savenko (Moscow State University of Psychology and Education, 2024)
Global social transformations affected people are taking place in the modern world. This influence can negatively affect representatives of the younger generation – students who do not have personal and social maturity and are in the process of professional development. The problem of the study is to identify the resources for psychological safety of students in a tense sociocultural environment. The article presents a review of scientific works from 2019 to 2023 using the electronic bibliographic databases RSCI and Scopus. More than 70 scientific articles with the results of theoretical and empirical studies of the problem of human psychological safety resources in a tense sociocultural environment were analyzed. The studies involved civilians living in territories with special conditions, including territories of military conflicts: teenagers, adults, students. Based on the results of a systematic review, a theoretical model is proposed. It includes external and internal resources for the psychological safety of students in a tense sociocultural environment. The features of students' socialization and the resources of the educational environment are identified as key external resources. Internal ones include cognitive regulation of emotions, constructive defense mechanisms, prosocial values and social intelligence, which act as the main resources for overcoming traumatic experiences, influencing subjective well-being and ensuring the psychological safety of students. The proposed theoretical model can serve as the basis for the development of psychological support programs for students. Research prospects can be presented in the context of empirical verification of the theoretical model.